2021
DOI: 10.1111/1750-3841.15768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electric field treatment on the kinetics of rehydration, textural properties, and the extraction of intracellular compounds of dried chickpeas

Abstract: This study investigated the effect of pulsed electric fields (PEF) pretreatment on rehydration kinetics, firmness, and release of intracellular components of dried chickpeas during rehydration at 35 to 65°C. After soaking preconditioning, chickpeas were subjected to PEF treatments (2.5 and 3.3 kV/cm, 0.2 to 12.0 kJ/kg, 15 µs pulse width, 20 Hz frequency). PEF treated and untreated chickpeas were dried in crossflow air dryer and their rehydration at constant seed/water ratio of 1:5 was studied for 24 hr. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Air‐drying energy consumption ( W DR ) was evaluated for all studied samples, in order to estimate the potential energy savings obtained from the use of either OD or PEF as pretreatments or the combined effect of PEF and OD processes before air‐drying. The W DR was calculated as a ratio of the total energy consumed to achieve 80% moisture reduction, according to Equation (8) (Andreou et al., 2021a,b): WDRbadbreak=A·v·ρair·tAD·normalΔT·Cpm0\begin{equation}{W_{{\rm{DR}}}} = \frac{{A \cdot v \cdot {\rho _{{\rm{air}}}} \cdot {t_{{\rm{AD}}}} \cdot {{\Delta}}T \cdot {C_{\rm{p}}}}}{{{m_0}}}\;\end{equation}where A = 0.2886 m 2 , v = 1.5 m/s, ρ air (at 60°C and atmospheric pressure, 1 atm) = 1.029 kg/m 3 , C p (at 60°C and atmospheric pressure 1 atm) = 1.009 kJ/kg/K, and m 0 = 0.3 kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Air‐drying energy consumption ( W DR ) was evaluated for all studied samples, in order to estimate the potential energy savings obtained from the use of either OD or PEF as pretreatments or the combined effect of PEF and OD processes before air‐drying. The W DR was calculated as a ratio of the total energy consumed to achieve 80% moisture reduction, according to Equation (8) (Andreou et al., 2021a,b): WDRbadbreak=A·v·ρair·tAD·normalΔT·Cpm0\begin{equation}{W_{{\rm{DR}}}} = \frac{{A \cdot v \cdot {\rho _{{\rm{air}}}} \cdot {t_{{\rm{AD}}}} \cdot {{\Delta}}T \cdot {C_{\rm{p}}}}}{{{m_0}}}\;\end{equation}where A = 0.2886 m 2 , v = 1.5 m/s, ρ air (at 60°C and atmospheric pressure, 1 atm) = 1.029 kg/m 3 , C p (at 60°C and atmospheric pressure 1 atm) = 1.009 kJ/kg/K, and m 0 = 0.3 kg.…”
Section: Methodsmentioning
confidence: 99%
“…The cost of OD process was estimated at the selected optimal conditions (55 • C, 120 min, 1/5 (ws/w OD ) and formulation of OD solution (40% glycerol, 10% trehalose, 10% galacto-oligosaccharides, 2.0% ascorbic acid, 2.0% sodium chloride, and 1.5% calcium chloride in strained yoghurt whey). It was estimated that the OD solution cost would be approximately 0.33€/kg fresh pumpkin, assuming that the reconstitution of OD solution would be at least 5 times, as suggested by literature (Andreou et al, 2021a(Andreou et al, , 2021b. The total cost of the OD process was estimated at approximately 0.35€/kg pumpkin.…”
Section: Optimal Processing Conditionsmentioning
confidence: 99%
“…Limitations in the large-scale application of PEF treatment of food grains and the way forward A recent study observed that thermal processing above 90 • C without calcium addition should be avoided to prevent the severe degradation of texture parameters (up to 70%) of PEF-treated beans due to loss of structural integrity caused by increased temperature (Alpos et al, 2022). From an industrial perspective, the production of legumes with a decreased rehydration time before cooking and the simultaneous release of undesirable carbohydrates is expected to have a higher level of customer acceptance (Andreou et al, 2021). Moreover, PEF treatment can destroy cell membranes and alter the mechanical properties of plant tissues, leading to changes in their physical and textural properties.…”
Section: 32mentioning
confidence: 99%
“…In another study, PEF pretreatment resulted in softening of chickpea tissues owing to a faster rate of water uptake during rehydration. With the increasing intensity of PEF treatment (> 3.6 kJ/kg), the firmness of samples rapidly decreases (Andreou et al., 2021). Amylolytic enzymes hydrolyze the glycosidic linkages in starch to produce soluble maltose and glucose (Barman & Dkhar, 2015).…”
Section: Effects Of Emerging Nonthermal Technologies On Food Grain Te...mentioning
confidence: 99%
“…Postharvest treatment plays an important role in improving the storage life of fruits and vegetables. Pulsed electric fields ( 5 ), heating ( 6 ), cold plasma technology ( 7 ), edible coating ( 8 ), and pulsed light ( 9 ) are some of the emerging technologies for postharvest treatments. Currently, attention is focused on ozone as a powerful antibacterial agent, characterized by rapid decomposition and oxidation, and is approved by the U.S. Food and Drug Administration as an antibacterial additive in direct contact with food.…”
Section: Introductionmentioning
confidence: 99%